Ionospheric Response to the Space Weather Events of 4-10 September 2017: First Chilean Observations - Bravo, Manuel; Villalobos, Carlos; Leiva, Rodrigo; Tamblay, Luis; Vega-Jorquera, Pedro; Ovalle, Elías; Foppiano, Alberto
Objective: The diurnal variations of several ionospheric characteristics during the Space Weather Events of 4-10 September 2017, for Chilean latitudes, will be reported. Materials and Methods: Observations were made using a recently installed ionosonde at the Universidad de La Serena field station (29°52'S; 71°15’W). Also, reported is the total electron content determined using the upgraded Chilean network of dual-frequency Global Navigation Satellite Systems (GNSS) receivers. Results: Sudden ionospheric disturbances are described in terms of the minimum reflection frequency determined from ionosonde records. An attempt to derive the extent of the effect on high frequency propagation paths in the region is made using simultaneous ionosonde observations at other locations. The geomagnetic storm ionospheric effects are discussed in detail using the observed diurnal variation of maximum electron concentration (NmF2), virtual height of the F-region (h’F/F2) and Total Electron Content (TEC). These are complemented with the time-latitude variation of TEC for the 70°W meridian. Conclusion: It is found that large increases of NmF2, h’F/F2 and TEC observed during 8 September 2017 storm are well described in terms of the evolution of the Equatorial Ionospheric Anomaly (EIA) over the same time interval. Known physical mechanisms are suggested to explain most of the observations.